粗对苯二甲酸加氢精制催化剂 (2018)
本发明涉及粗对苯二甲酸加氢精制催化剂、催化剂的制备方法，以及粗对苯二甲酸加氢精制方法，主要解决现有技术中存在的加氢过程中副产物多的问题，本发明通过采用粗对苯二甲酸加氢精制催化剂，所述催化剂包括载体和活性组分，所述的载体为二氧化钛；所述活性组分包括钯和钌，钯的质量百分含量为催化剂干重的0.3～0.8％，钌与钯的质量之比为(0～4)：4的技术方案，较好地解决了该技术问题，可用于粗对苯二甲酸加氢精制生产中。 The invention relates to a crude terephthalic acid hydrofining catalyst and a preparation method thereof, and a crude terephthalic acid hydrofining method, and is used for mainly solving the problem that a hydrogenation process has many by-products in the prior art. The technical problem is better solved through adopting the technical scheme that the crude terephthalic acid hydrofining catalyst is provided, the catalyst includes a carrier and active components, the carrier is titanium dioxide, the active components include palladium and ruthenium, the mass percentage of palladium is 0.3-0.8% of the dry weight of the catalyst, and the mass ratio of ruthenium to palladium is (0-4) to 4. The catalyst can be used in crude terephthalic acid hydrofining production.